English-language training at a maritime university as a mandatory condition for the successful professional activity of a deck officer - Regina Vladislavovna Drazhan (Вестник Майкопского государственного технологического университета)
The relevance of the research is determined by the increasing risks related to incorrect communication both professional and interpersonal ones within the ship crew, which, in turn, emphasizes the importance of professional English-language training for a navigator, which begins during the period of study at a university and lasts throughout the entire career. The requirements for proficiency in professional English-language communication are regulated by international standards, which is of great importance in assessing the professional competence of a navigator. The research problem is as follows: how does English-language vocational training at a maritime university affect interpersonal relations in mixed crews, the professional growth of a sailor and reduce the risks in his professional activity? The aim of the study is to determine the main tasks of a university professional English-language training in the format of negotiating at sea in order to minimize possible risks in the work of a deck officer. The research methods used are analysis, synthesis, generalization. The experimental base was the Institute of Water Transport named after G.Ya. Sedov. The research results. Professional risks of a navigator have been analyzed, factors and consequences of risks at sea have been identified; the meanings of the concepts of «language barrier», «human factor», «barrier of misunderstanding», «communicative risk» have been disclosed; the influence of flexible skills on the safety of life and work in a team have been substantiated; the theory of continuous professional English-speaking training of seafarers has been described. Key findings: communication skills of navigators should be formed by integrating English into the disciplines of the professional cycle; the introduction of modern educational technologies in the process of teaching professional maritime English, continuous professional development of English teachers. Development of social partnership will increase the efficiency of the process itself.